Early Introduction of Cenobamate in Uncontrolled Focal Epilepsy: Insights from a Structured Controversy - Angelo Labate; Claudio Liguori; Elena Tartara; Gemma Tumminelli; Annacarmen Nilo; Marta Piccioli; Filippo Dainese; Luigi Del Gaudio; Carlo Di Bonaventura (Neurology and Therapy)
Abstract Introduction Drug-resistant focal epilepsy, as defined by the International League Against Epilepsy (ILAE), is characterized by the failure to achieve seizure control despite the use of at least two appropriately chosen and adequately dosed antiseizure medications (ASMs). This condition affects approximately 30% of patients and represents a significant clinical challenge. Cenobamate, a novel ASM with a unique dual mechanism of action—enhancing inhibitory GABAergic currents and attenuating persistent sodium currents—has emerged as a promising therapeutic option for drug-resistant focal epilepsy. Methods This expert consensus document was developed using a structured controversy methodology, integrating real-world experience and a narrative review of the literature focusing on the role of cenobamate in the management of drug-resistant focal epilepsy. This manuscript synthesizes current evidence on cenobamate and provides clinical recommendations for its integration into epileptological practice. Results The expert panel findings support the early use of cenobamate following the failure of two ASMs, emphasizing its efficacy in achieving substantial seizure reduction and increasing the likelihood of seizure freedom. Early prescription of cenobamate may offer a valuable therapeutic opportunity for patients with refractory focal epilepsy, potentially reducing seizure-related complications and improving quality of life. Identified challenges include limited long-term safety data in specific populations and regional disparities in drug access. Conclusion Cenobamate represents a significant advancement in the treatment of drug-resistant focal epilepsy. Its early adoption in clinical practice has the potential to enhance patient outcomes. The expert panel provides recommendations that underscore individualized treatment planning, close monitoring during titration, and advocacy for improved accessibility. Continued research and policy initiatives are essential to fully realize the therapeutic potential of cenobamate.